Rice : origin, antiquity and history - Sharma, S. D. , 1934- (Science Publishers ; Distributed by CRC Press, 2010)
Man has improved the rice plant, increased its productivity and has found various uses of its parts. The story of rice differs from region to region and has been different in different periods of time. This book provides an interesting reading of such events in the course of its 9000 years long history